The New Application of UHPLC-DAD-TOF/MS in Identification of Inhibitors on β-Amyloid Fibrillation From Scutellaria baicalensis - Yu, Lu; Wu, An-Guo; Wong, Vincent Kam-Wai; Qu, Li-Qun; Zhang, Ni; Qin, Da-Lian; Zeng, Wu; Tang, Bin; Wang, Hui-Miao; Wang, Qiong; Law, Betty Yuen-Kwan (Frontiers in Pharmacology, 2019)
Literary evidence depicts aggregated amyloid β (Aβ) leads to pathogenesis of Alzheimer’s disease (AD). Although many traditional Chinese medicines (TCMs) are effective in treating neurodegenerative diseases, there is no effective way for identifying active compounds from their complicated chemical compositions. Instead of using traditional herbal separation method with low efficiency, we herein applied UHPLC-DAD-TOF/MS for accurate identification of active compounds inhibiting the fibrillation of Aβ (1-42), via evaluation of peak area of individual chemical components in chromatogram after incubation with Aβ peptide. By using the neuroprotective herbal plant Scutellaria baicalensis (SB) as a study model, the inhibitory effect on Aβ by its individual compounds were validated by thioflavin-T (ThT) fluorescence assay, biolayer interferometry analysis, dot immunoblotting and native gel electrophoresis after UHPLC-DAD-TOF/MS analysis. The viability of cells after Aβ (1-42) incubation was further evaluated by both MTT assay and flow cytometry analysis. 13 major chemical components in SB were identified by UHPLC-DAD-TOF/MS after incubation with Aβ (1-42). The peak areas of 2 components from SB, baicalein and baicalin, were significantly reduced after incubating with Aβ (1-42) as compared to compounds alone without incubation with Aβ (1-42). Consistently, both compounds inhibit the formation of Aβ (1-42) fibrils, increase the viability of cells after Aβ (1-42) incubation. Based on the hypothesis that active chemical components have to possess binding affinity to Aβ (1-42) for inhibiting its fibrillation, a new application of using UHPLC-DAD-TOF/MS for accurate identification of inhibitors from herbal plants on Aβ (1-42) fibrillation is developed.